Development of E-Module Ecosystem Material in Class V Science Learning in MI/SD - Idayanti, Zulfi; Budiarti, Eriska Witantri; Suleman, Muh. Asharif (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2024)
The development of e-modules has become an innovative solution in enhancing the quality of science learning, particularly in elementary and Islamic elementary schools (MI/SD). This study aims to produce an additional learning resource kind of e-module by using the software flip PDF professional which convert a PDF files become an interactive e-modules that contain an IPA material ecosystem. The e-modules integrates interactive multimedia, visual aids, and self-assessment tool, aligned with the class V curriculum to facilitate independent and active learning without having to wait for the help of educators. This study focuses on the development of an e-module for ecosystem materials in class V. The research employed the 4D model, through several stages, namely: (1) Definition stage: analyzing the 2013 curriculum KI and KD, analyzing questionnaires filled out by teachers from various regions, and problems in the field. (2) Planning stage: compiling the outline of the E-Module, compiling the E-Module framework, compiling the contents of the E-Module, preparing tools and materials, and compiling research instruments. (3) Development stage: validation carried out by material experts and media experts and practicality testing by educational practitioners and students. The E-Module quality assessment from material experts in the first stage received an average score of 3.80 and fell into the "good" category. After revision and assessment at stage 2, the average score was 4.28 and entered the "Very Good" category. The E-Module quality assessment from media experts received an average score of 4.05 and fell into the "good" category. Thus, this e-module is declared to have quality and can be used as an additional learning resource for students in class V MI/SD. The practicality test by educational practitioners obtained an average score of 4.40 and 4.52 by category. "Very good". Student responses received an average score of 4.74 in the "Very Good" category.